2011
DOI: 10.5820/aian.1802.2011.17
|View full text |Cite
|
Sign up to set email alerts
|

"It Runs in the Family": Intergenerational Transmission of Historical Trauma among Urban American Indians and Alaska Natives in Culturally Specific Sobriety Maintenance Programs

Abstract: The aim of this exploratory study, which was informed by ethnographic principles, was to better understand the intergenerational transmission of historical trauma among urban American Indians/Alaska Natives (AI/ANs) in culturally specific sobriety maintenance programs. The results of the study were organized into 3 overarching categories, which included 10 themes that emerged contextually in relation to participants' lived experience of historical and associated traumas, substance abuse, and current involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 28 publications
0
75
0
1
Order By: Relevance
“…Lichenstein and Annas (2000) found there is a relationship between a parent having a fear and children developing the same fear due to vicarious learning. This seems to be substantiated by Myhra's (2011) findings that all 13 participants in a qualitative study examining the relationship between substance use and historical trauma in Native American adults believed that historical trauma was key to their elders' dysfunctional behavior-in particular, substance abuse. One participant characterized it as "monkey see, monkey do," in that she was following her family's pattern of abusing substances and being involved in abusive interpersonal relationships (Myhra, 2011, p. 26).…”
Section: Cross-generational Trauma Transmissionmentioning
confidence: 71%
See 1 more Smart Citation
“…Lichenstein and Annas (2000) found there is a relationship between a parent having a fear and children developing the same fear due to vicarious learning. This seems to be substantiated by Myhra's (2011) findings that all 13 participants in a qualitative study examining the relationship between substance use and historical trauma in Native American adults believed that historical trauma was key to their elders' dysfunctional behavior-in particular, substance abuse. One participant characterized it as "monkey see, monkey do," in that she was following her family's pattern of abusing substances and being involved in abusive interpersonal relationships (Myhra, 2011, p. 26).…”
Section: Cross-generational Trauma Transmissionmentioning
confidence: 71%
“…Given that the atrocities that were inflicted on the Native American people were substantive, it seems understandable that transmission of historical loss symptoms could occur via this pathway to the children. In fact, Myhra (2011) found that Native American participants connected "the impact of elders' stories of historical trauma and loss, and their own traumatic experiences, to intrusive thoughts about these ordeals and to fear that trauma will continue for future generations" (p. 25).…”
Section: Cross-generational Trauma Transmissionmentioning
confidence: 99%
“…Substance abuse in AI families has been linked to experiences of psychological and cultural trauma; although traumatic experiences have decreased overtime and for younger generations, their rate still remains high compared with other racial and ethnic groups (Myhra & Wieling, in press). The feelings of being an outsider in society, often related to racism and discrimination, has been linked to substance abuse among AIs (Myhra, 2011;Spicer, 1998). This may help explain findings from a three generation family study in whi ch older generations presented with less perceived control (Grob, Weisheit, & Gomez, 2009).…”
Section: American Indians and Substance Abusementioning
confidence: 79%
“…Thus, for AI families who contend with historical, cultural, and complex traumas, the result may be the development of maladaptive survival or coping strategies. Among AI adults in recovery, the intergenerational nature of alcoholism has been clearly established, as well as the need for families to transmit strength, hope, and healing to younger generations (Lowery, 1999;Myhra, 2011;Walters et al, 2002;Whitbeck, 2006). AIs continue to heal together as families and communities by using their greatest assets of spirituality and cultural practices (Duran, 2006;Jervis & AI-SUPERPFP team, 2009;Walters, 1999) to rise above what some believed to be "a predetermined fate" of intergenerational substance abuse and related problematic patterns (Myhra, 2011, p. 36).…”
Section: American Indians and Substance Abusementioning
confidence: 99%
See 1 more Smart Citation